An overview of adjuvants utilized in prophylactic vaccine formulation as immunomodulators - Nidhi Chauhan; Sukirti Tiwari; Tessy Iype; Utkarsh Jain (Taylor & Francis Group, 2017)
Introduction: Development of efficient and cost effective vaccines have been recognized as the primary concern to improve the overall healthcare in a country. In order to achieve this goal, more improved and powerful adjuvants need to be developed. Lacking in the self-adjuvanting immuno-modulatory constituents, vaccines exhibit lower immunogenicity. Combining potent adjuvants with vaccines is the most appropriate method to enhance the efficacy of the vaccines. Hence, this review is focussed on the most potent adjuvants for the formulation of vaccines. Areas covered: This review focuses on Oil-based emulsions, Mineral compounds, Liposomes, Bacterial products, ISCOMs and most recently used nanomaterials as adjuvants for enhancing the antigenicity of vaccines. Furthermore, this review explains the immunological response elicited by various particles. Moreover, case studies are incorporated providing an in depth analyses of various adjuvant-containing vaccines which are currently used. Expert commentary: Enhanced fundamental knowledge about the adjuvants and their immuno-stimulatory capabilities and delivery mechanisms will facilitate the rational designing of prophylactic vaccines with better efficacy.